Probing Mechanisms and Therapeutic Potential of γ-Secretase in Alzheimer’s Disease - Michael S. Wolfe (Molecules, 2021)
The membrane-embedded γ-secretase complex carries out hydrolysis within the lipid bilayer in proteolyzing nearly 150 different membrane protein substrates. Among these substrates, the amyloid precursor protein (APP) has been the most studied, as generation of aggregation-prone amyloid β-protein (Aβ) is a defining feature of Alzheimer’s disease (AD). Mutations in APP and in presenilin, the catalytic component of γ-secretase, cause familial AD, strong evidence for a pathogenic role of Aβ. Substrate-based chemical probes—synthetic peptides and peptidomimetics—have been critical to unraveling the complexity of γ-secretase, and small drug-like inhibitors and modulators of γ-secretase activity have been essential for exploring the potential of the protease as a therapeutic target for Alzheimer’s disease. Such chemical probes and therapeutic prototypes will be reviewed here, with concluding commentary on the future directions in the study of this biologically important protease complex and the translation of basic findings into therapeutics.